Comparative Study of Morphological Characteristics and Body Composition between Elite Basketball Players from Different Regions - Bojan Masanovic; Marina Vukotic; Velisa Vukasevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The purpose of this study was to describe morphological characteristics and body composition of the basketball players from elite ranking of the competition Montenegro and Serbia as well as to make comparation between them. Forty-eight males were enrolled in the study, divided into two groups: twenty-four senior players from the First Basketball League of Montenegro and twenty-four senior players from the Serbian Superleague. Morphological characteristics were evaluated by a battery of four variables: body height, body weight, arm span and length of the leg. Body composition were evaluated by a battery of two variables: body mass index and fat percentage of body. The standard central and dispersive parameters of all variables were calculated. The signifi cance of the diff erences between the Second League basketball players from Montenegro and Serbia was determined by a t-test for small independent samples . The results showed that a signifi cant diff erences was no found for any variable among the group. Therefore, these fi ndings may give coaches knowledge that Montenegrin players have a good morphological potential, in that segment are not lagging behind for the Serbian players, whose players make excellent results at international competitions.